Penggunaan Bahasa Gaul Generasi Z Perspektif Komunikasi Islam: Studi pada Mahasiswa Fakultas Dakwah dan Komunikasi UIN Sumatera Utara - Cindy Satika Lesmana; Faridah Faridah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The use of slang is a common phenomenon that occurs on campus. According to the perspective of Islamic communication, the use of slang must be in accordance with the principles of Islamic communication, namely qaulan sadida, qaulan baligha, qaulan maysura, qaulan layyina, qaulan karima, and qaulan Ma'rufa. This research aims to analyze the form of slang communication of Generation Z students of the Faculty of Da'wah and Communication of UIN Sumatra Utara in the perspective of Islamic Communication. This research uses a qualitative method with a symbolic interaction approach. Data were collected through observation, interviews, and literature studies. The results showed that there are many forms of slang communication of Generation Z students in the Faculty of Da'wah and Communication of UIN Sumatra Utara and not all of them have negative connotations. Students use slang as a means of self-expression and social interaction, especially in informal situations, in formal communication, they prefer to use formal language. From the perspective of Islamic communication, slang can be incompatible with the principles of Islamic communication if used in the wrong context and place. Slang can also be utilized as a da'wah communication strategy that is more inclusive and easily accepted by Generation Z.